APPLICATION OF COOPERATIVE LEARNING MODEL INDEX CARD MATCH TYPE IN IMPROVING STUDENT LEARNING RESULTS ON COMPOSITION AND COMPOSITION FUNCTIONS OF FUNCTIONS INVERS IN MAN 1 MATARAM - Syahrir Syahrir (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
Lack of student response in learning mathematics caused by passive of student in process of learning progress so that student consider mathematics subject is difficult subject to be understood. The research is Classroom Action Research (PTK) using 2 cycles, then the purpose of this research is how the implementation of cooperative learning type of index card match in improving student learning outcomes on the subject matter of composition function and inverse function in MAN 1 Mataram. While the results of the analysis in the study showed that there is in cycle I obtained classical completeness 78.79% with the average score of student learning outcomes 69.78 and the average value of student learning responses with the category Enough, then in cycle II shows that classical thoroughness 87 , 89% with mean score of student learning result 78,94 and average value of student learning response with good category. So it can be concluded that the implementation of Model Cooperative Learning Type Index Card Match can improve student learning outcomes on the subject matter of composition function and inverse function.